2022
DOI: 10.1007/s13399-022-03569-9
|View full text |Cite
|
Sign up to set email alerts
|

Deep eutectic solvents for the extraction of β-chitin from Loligo vulgaris squid pens: a sustainable way to valorize fishery by-products

Abstract: β-chitin, a promising biopolymer for the production of chitosan and biomaterials, is sourced from fishery by-products. Herein, β-chitin has been extracted using Deep Eutectic Solvents (DES) for the first time, only the α-polymorph having been extracted using these solvents until now. Six acid, neutral, and alkaline DES systems were trialed, with only the alkaline DES systems, in particular potassium carbonate: glycerol (KGLY) at 100 or 120 °C for 2 or 3 h, resulting in high-purity β-chitin. The ensuing β-chiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…DES coupled with potassium carbonate: glycerol enhances the purity of β-chitin from snail shell and squid pen at 100 or 120 • C for 2 or 3 h. So far, this combination of solvents has been used only for α-polymorph. But, these results proved that DES is efficient β-polymorph as well (Kimi & Hamdi, 2023;McReynolds et al, 2022). Other physical properties such as acetylation degree and crystallinity improved between 77% and 88%, and 88% and 91%, respectively, and a maximum degradation temperature was around 350 • C. DES used in this extraction was recovered and recycled over three times without modifying the final yield of chitin (30%) and C/N ratio (6.45-6.52).…”
Section: Deep Eutectic Solvent (Des) Extraction Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…DES coupled with potassium carbonate: glycerol enhances the purity of β-chitin from snail shell and squid pen at 100 or 120 • C for 2 or 3 h. So far, this combination of solvents has been used only for α-polymorph. But, these results proved that DES is efficient β-polymorph as well (Kimi & Hamdi, 2023;McReynolds et al, 2022). Other physical properties such as acetylation degree and crystallinity improved between 77% and 88%, and 88% and 91%, respectively, and a maximum degradation temperature was around 350 • C. DES used in this extraction was recovered and recycled over three times without modifying the final yield of chitin (30%) and C/N ratio (6.45-6.52).…”
Section: Deep Eutectic Solvent (Des) Extraction Methodsmentioning
confidence: 91%
“…The extraction process requires an acidic solution to act as a co-solvent hydrogen bond donor. Recently, McReynolds et al (2022) reported that DES breaks strong hydrogen bonds between chitin amino groups and H + by using citric acid, malonic acid, and lactic acid. These green solvents are highly biodegradable and less or nontoxic nature compared to conventional alkali extraction (Zhang et al, 2012).…”
Section: Deep Eutectic Solvent (Des) Extraction Methodsmentioning
confidence: 99%
“…In this sense, although Lv et al did not mention the residual protein and mineral content in chitin, they proved that, using an alkaline DES (K 2 CO 3 -Glycerol), they were capable to remove 64.53% and 1.07% of proteins and minerals, respectively [150]. McReynolds et al [151] also investigated the extraction of chitin from squid pens using acidic, neutral, and alkaline DESs. They conducted a comparison with yields obtained through conventional chemical methods and observed significantly higher yields with acidic and neutral DESs, attributed to their limited demineralization and deproteinization capabilities.…”
Section: Des-assisted Chitin Extractionmentioning
confidence: 99%
“…The scientific publications related to the chitin/chitosan and collagen value chains analysed in the present study focused mostly on how these bioactive compounds and/or their derivatives were obtained rather than on the later steps of both value chains and market-related information. Interestingly, more publications mentioned [70,[149][150][151] the origin of raw materials, inputs/feedstock, and the pre-treatment and pre-processing steps in the collagen value chain than in the chitin/chitosan value chain, but the opposite trend was found [65,110,152] for processing and product manufacturing, consumption, chain outputs, and the interaction between stakeholders. This switch may indicate that the focus of scientific publications related to the chitin/chitosan value chain is changing towards the final steps.…”
Section: Trends In Data Distribution Along Each Value Chainmentioning
confidence: 99%